Syngas production through gasification of coal water mixture and power generation on dual-fuel diesel engine. Issue 2 (April 2019) - Oh, Gunung; Ra, Ho Won; Yoon, Sung Min; Mun, Tae Young; Seo, Myung Won; Lee, Jae-Goo; Yoon, Sang Jun
Abstract: In the present study, a syngas was produced by preparing coal water mixtures of two different concentrations and gasifying the coal water mixtures. An entrained-flow gasifier of 1 ton/day scale was used and, after undergoing a purification process, the produced syngas was applied to a modified diesel engine for power generation. As the gasification temperature increased, the carbon conversion and the cold gas efficiency were found to increase. In the composition of the produced syngas, the content of H2 remained constant, that of CO increased, and those of CO2 and CH4 decreased. The carbon conversion increased with equivalence ratio. A maximum cold gas efficiency of 66.1% was found at the equivalence ratio of 0.43. N2 was additionally supplied to verify the gasification characteristics depending on the gas feed flow rate. The optimum feed flow rate was verified at different slurry concentrations and equivalence ratio. The produced syngas was supplied to a modified diesel engine and operated depending on the syngas feed flow rate and the engine operation conditions. The brake thermal efficiency of the engine was constant regardless of the syngas feed flow rate. The diesel engine showed high efficiency despite the mixing of the syngas. Highlights: Gasification of two different concentration of CWM was performed and compared. H2 /CO ratio in syngas was affected by concentration of coal water mixtures. Optimal feed flow rate of gasification agent was found. Power generation using syngas on dual-fuel diesel engine showed high efficiency.